Impact Of Spatial Ability Training And Its Transfer - Samsudin, Khairulanuar (2010)
This study was undertaken to examine students\' perceived ability to learn basic engineering drawing, differential impacts of spatial training and training transfer. The research method used was based on the Triangulation Software Development Method, which was carried out in two parts: a survey Research, and an Experimental Research.